2023
DOI: 10.3390/v15040912
|View full text |Cite
|
Sign up to set email alerts
|

The Lytic Activity of Bacteriophage ZCSE9 against Salmonella enterica and Its Synergistic Effects with Kanamycin

Abstract: Salmonella, the causative agent of several diseases in humans and animals, including salmonellosis, septicemia, typhoid fever, and fowl typhoid, poses a serious threat to global public health and food safety. Globally, reports of therapeutic failures are increasing because of the increase in bacterial antibiotic resistance. Thus, this work highlights the combined phage–antibiotic therapy as a promising approach to combating bacterial resistance. In this manner, the phage ZCSE9 was isolated, and the morphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…In the study by Islam et al [ 46 ], the latent period for salmophage LPST153 was 10 min, and the burst size was 113 ± 8 PFU cell −1 . In turn, in the study by Abdelsattar et al [ 47 ], the latent period for the salmophage ZCSE9 was 10 min, but the burst size was about 20 PFU cell −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Islam et al [ 46 ], the latent period for salmophage LPST153 was 10 min, and the burst size was 113 ± 8 PFU cell −1 . In turn, in the study by Abdelsattar et al [ 47 ], the latent period for the salmophage ZCSE9 was 10 min, but the burst size was about 20 PFU cell −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Abdelsattar et al [ 47 ], it was shown that the time necessary for adsorption of the maximum number of phages was almost 20 min for salmophage ZCSE9. Salmophage ZCSE9, in contrast to our two newly isolated phages, adsorbed very rapidly—within two minutes, it adsorbed 70% of viruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella enterica has been traditionally classified to different serotypes (serovars) and was reported that >2,500 serotypes cause most human infections ( Jackson et al, 2013 ). Many researches focus on identifying and characterizing the temperate phages for specific S. enterica serotypes, such as phage mTmV in S. enterica serotype Typhimurium ( S. typhimurium ) ST34 ( Tassinari et al, 2020 ), phage BIS20 in S. typhimurium ( Sattar et al, 2022 ), phage ZCSE9 in S. typhimurium ( Abdelsattar et al, 2023 ), phage SGP-C in S. enterica serotype gallinarum biovar gallinarum ( S. gallinarum ; Ilyas et al, 2022 ), phages vB_SenM-1, vB_SenM-2, vB_SenS-3 in 20 S. enterica serotypes, including S. heidelberg , S. panama , S. typhimurium , S. cholerasuis , S. enteritidis , S. virchow , etc. ( Kosznik-Kwasnicka et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they have the lowest bactericidal effect of 25 µg/mL for Bacillus cereus , 100 µg/mL for E. coli , S. aureus and S. enterica , 200 µg/mL for P. aeruginosa . Yet, when biofilm-AgNPs were combined with ZCSE9, which is specific for S. enterica 119 , its inhibitory and bactericidal effects were enhanced to have a higher effect in lower concentration, which is 3.1 µg/mL. These results were confirmed using a killing curve, which showed that when using biofilm-AgNPs with its MIC, it would inhibit the growth of the bacteria for up to 11 h. This long period of time might indicate the long-lasting effect of the biofilm-AgNPs.…”
Section: Discussionmentioning
confidence: 99%